PENGARUH PENERAPAN PENGENDALIAN INTERNAL DAN GOOD CORPORATE GOVERNANCE TERHADAP PENCEGAHAN FRAUD PADA PERBANKAN DI KOTA KUPANG - Tiara Fitriana Azhari; Anthon Simon Y. Kerihi; Novi Theresia Kiak (JURNAL AKUNTANSI, 2022)
This research aims to determine the effect of internal control and good corporate governance partially and simultaneously towards fraud prevention in Banking at Kupang City. This type of research is quantitative. The sampling technique was purposive sampling and the total of samples in this research are 40 respondents. The method of collecting data in this research is using quisionnaire. Data analysis technique used in this research was multiple line regression analysis and processed using the analysis tool SPSS 25. The results of this research indicate that internal control partially did not affect on fraud prevention, while good corporate governance partially affect on fraud prevention. And simultaneously the internal control and good corporate governance affect on fraud prevention in Banking at Kupang City.